Electronic Control Unit (ECU) developmentof a fuel injection system - Aziz, Azeera (2013)
In order to meet the limits imposed on automotive emissions, engine control systems are required to constrain air/fuel ratio (AFR) in a narrow band around the stoichiometric value, due to the strong decay of catalyst efficiency in case of rich or lean mixture. This project focuses on the design and development of a control system to reduce the waste of automotive exhaust emission. A model of a sample sparks ignition engine and Simulink’s capabilities to model an internal combustion engine from the throttle to the crankshaft output are demonstrated based on analytical engine models that clearly describe engine’s air and fuel dynamic with no loss of engine system performance. Various mathematical models for the air to fuel ratio and control for spark ignition (SI) engines have been proposed to satisfy technical specifications. On this paper the mean value model and a simple effective linear engine model is used to get the value of air to fuel ratio. The controller is designed by using PID tuning method and FLC to develop for the engine dynamics model in order to target the desired output response. Simulation results demonstrate that better performance can be achieved with PID controller than FLC. The actual response specification with PID controller and FLC matched the desired response specifications.